Realism and antirealism in Kant's moral philosophy : new essays - Santos, Robinson dos, 1975-; Schmidt, Elke Elisabeth (Kantstudien. Ergänzungshefte, 2018)
"The debate between moral realism and antirealism plays an important role in contemporary metaethics as well as in the interpretation of Kant's moral philosophy. This volume aims to clarify whether, and in what sense, Kant is a moral realist, an antirealist, or something in-between. Based on an explication of the key metaethical terms, internationally recognized Kant scholars discuss the question of how Kant's moral philosophy should be understood in this regard. All camps in the metaethical field have their inhabitants: Some contributors read Kant's philosophy in terms of a more or less robust moral realism, objectivism, or idealism, and some of them take it to be a version of constructivism, constitutionism, or brute antirealism. In any case, all authors introduce and defend their terminology in a clear manner and argue thoughtfully and refreshingly for their positions." -- VitalSource description.